2009
DOI: 10.1039/b904745j
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the non-resonant chemical mechanism of SERS using a molecular photoswitch

Abstract: In this work we present a detailed investigation of the Raman properties of a dithienylethene photoswitch interacting with a small gold cluster (Au(19)(+)) using time-dependent density functional theory (TD-DFT). The enhancement mechanism (CHEM) due to the molecule-surface chemical coupling in surface-enhanced Raman scattering (SERS) has been characterized for this system. We demonstrate that it is possible to control the CHEM enhancement by switching the photoswitch from its closed form to its open form. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
2
17
0
2
Order By: Relevance
“…It is clearly displayed that a fair correlation between the model enhancements EFintmodel and the DFT calculated integrated enhancements EF int , although the two‐state model deviates by as much as a factor of 4. The deviations between the model and the DFT results may be due to the fact that for the chemisorbed systems, a single ω¯DMABAu is not enough to describe the system due to strong orbital mixing and more than two states should be used in describing the chemical enhancements, as previously reported for the benzenethiols chemisorbed on the gold clusters . In spite of these deviations, the model well predicts the change trend in the CHEM enhancement for the trans‐DMAB and cis‐DMAB adsorbed on the cluster Au n .…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…It is clearly displayed that a fair correlation between the model enhancements EFintmodel and the DFT calculated integrated enhancements EF int , although the two‐state model deviates by as much as a factor of 4. The deviations between the model and the DFT results may be due to the fact that for the chemisorbed systems, a single ω¯DMABAu is not enough to describe the system due to strong orbital mixing and more than two states should be used in describing the chemical enhancements, as previously reported for the benzenethiols chemisorbed on the gold clusters . In spite of these deviations, the model well predicts the change trend in the CHEM enhancement for the trans‐DMAB and cis‐DMAB adsorbed on the cluster Au n .…”
Section: Resultsmentioning
confidence: 77%
“…In addition, it is demonstrated that Raman signal intensities of the adsorbed trans‐DMAB and cis‐DMAB for the Au 19 –DMAB–Au 19 junctions, are further enhanced as compared to the corresponding DMAB–Au 19 complexes and the chemical enhancement of the trans conformation is much larger than that of the cis conformation, which is described by the induced polarizability. In recent years, some researchers employed SERS spectroscopy to probe the molecular configurations and investigate the strong electronic coupling between functionalized molecule and metal to better understand chemical contribution to SERS. We expect that our findings could yield new insights into detecting the photoswitchable azobenzenes anchored on the metal substances and understanding chemical contribution to SERS activity tuned by their conformation transitions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enhancement factor contributing to SERS depends on the magnitude of the localized electromagnetic field as ~E 4 [24]. The chemical mechanism also contributes to signal enhancement for certain molecules, with charge transfer in molecules at the metal–molecule interface [25,26]. Regardless of the mechanism, SERS strategy provides a “fingerprint-like” Raman spectrum that is unique to the excited molecule used.…”
Section: Surface-enhanced Raman Scattering As Readout Strategy—mecmentioning
confidence: 99%